Inovasi Modul Digital Berbasis Eksplorasi Konsep Fisika Bermuatan Kearifan Lokal "Pembuatan Jajanan Tradisional" Guna Mendukung Terbentuknya Profil Pelajar Pancasila - Eti Elisa; Audri Mely Prabandari; Elma Tri Istighfarini; Haniyah Alivia; Latifa Widi Inayati H; Lailatul Nuraini (Jurnal Penelitian Pendidikan IPA, 2022)
Learning physics can be associated with the culture of society. Culture or local wisdom is the identity or characteristic of an area. Traditional snacks are important to be preserved because they are unique in terms of culture. Studies on the concept of physics in traditional snacks can be used as learning materials in the form of digital modules. This study aims to analyze the concept of physics in traditional snacks, as well as describe the effectiveness of using digital modules based on exploration of physics concepts containing local wisdom "traditional snacks" in order to realize Pancasila students. This research method is research & development with ADDIE development model. The result of the research is the identification of physical concepts in the traditional snacks of dawet, klepon, putu, egg rolls, and cotton candy. The physics concept is packaged in a digital module. The results of the digital module validation with a valid category (4.32). The n-gain result is 0.71 (high category) at SMAN 2 Jember, 0.69 (medium category) at SMAN 4 Jember and 0.37 (medium category) at SMAN 5 Jember. The results of student responses to digital modules for three school were 76.67% had a positive response category. Thus, this digital module can be used more widely as a learning medium to strengthen the profile of Pancasila students